The diverse functions of symbolism in Maqamat Imam al-Suyutiy - Kamis, Mohamad Faisal; Toklubok, Pabiyah; Mustapha, Nik Farhan; Wan Sulong, Wan Muhammad; Kamarudin, Kamariah; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Elements of symbolism in literary works are one of the essential elements discussed in any academic research. Symbolism is a medium to represent ideas and messages that the author wants to convey in his work. Meanwhile, Maqamat is a literary work which is loaded with symbols through the symbolic style of language and also has a message to convey. Therefore, this study is conducted to identify and analyse the functions of symbols in Maqamat Imam al-Suyutiy (MIS). This research is a qualitative study that uses the method of textual analysis. The research data was selected based on the elements of symbolism contained in the text of the speech taken directly from the five maqamat. In order to achieve the set objectives, the Nazm theory established by Abd al-Qahir al-Jurjaniy was used in this study. The analysis of context and co-text was conducted for all research data using this Nazm theory. The results showed that there were symbols such as flowers, fruits, gems, and fragrances used by the author. These symbols had several functions such as depicting the bad attitude of the government leaders, criticising the attitude of the members of the society, avoiding punishment by the rulers, expressing the discomfort of the MIS author about the political situation, and depicting the character of a person.